Aerobic granules in lab-scale bioreactor: a focus on size distribution and settling velocity properties / Azlina Mat Saad... [et al.] - Mat Saad, Azlina; Dahalan, Farrah Aini; Ibrahim, Naimah; Yusuf, Sara Yasina (Universiti Teknologi MARA Cawangan Pulau Pinang, 2017)
Biogranulation technology using aerobic granules is one of the most important discoveries in the field of wastewater treatment. This advanced technology is better than conventional wastewater treatment method because it is cost-effective and space-reduced. The evolution of aerobic granules from seed sludge to granules in sequencing batch reactor system was studied in this study. The purposes of this study are to measure the size of aerobic granules over time and to determine the settling velocity of the aerobic granules against time. The sequencing batch reactor system was operated in four processes involved feeding, aeration, settling and withdraw. The bioreactor was inoculated with seed sludge sample taken from wastewater treatment plant in Arau, Perlis and run at room temperature. Synthetic wastewater containing acetate and other elements were used to feed the biomass in the bioreactor system. The aerobic granules started to be detected in the sequencing batch reactor after two weeks of operation. The aerobic granules in size categories (>0.20.40.6 mm) had increased over the time. An increase of settling velocity (29.8 m/h) was observed in this present study. These findings demonstrate that the increase of aerobic granules size and settling velocity were important in determining the evolution of aerobic granules study.